Effects of Androctonus crassicauda (Olivier, 1807) (scorpiones: buthidae) venom on rats: correlation among acetylcholinesterase activities and electrolytes levels - Ozkan,O. (2007)
Scorpions can be considered living fossils because they have changed so little during the last 400 million years. They are venomous arthropods of the Arachnida class and regarded as relatives of spiders, ticks and mites. The aim of the present study was to evaluate the toxicity of Androctonus crassicauda (Olivier, 1807) venom and its effects on the acetylcholinesterase (AchE) activity and on electrolytes levels in rats. Animals were divided into seven groups of five rats each. Test groups received 250µg/kg of venom solution while control group was treated with 200µl of physiological saline solution (PSS). Blood samples were collected from the animals on the 1st, 2nd 4th, 8th, 12th, and 24th hours after subcutaneous injection of venom. Animals were monitored for 24 hours. Androctonus crassicauda venom significantly reduced AchE activity on the 12th hour when compared with control group. A statistically negative correlation between Na+ and K+ (p<0.05) and a positive correlation between Na+ and CL- (p<0.001) ions levels were observed after the administration of A. crassiccauda venom to rats. We can conclude that the differences in the electrolytes levels are due to acute renal failure, since elimination of toxin occurs primarily via the kidney.